A method for improving the interfacial strength of a fiber composite

CN122958736APending Publication Date: 2026-10-23XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510469939.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明提供一种提高纤维复合材料界面强度的方法,有效提高复合材料界面强度,解决传统方法中界面应力集中导致的界面失效问题

Benefits of technology

[0016]和现有技术相比,本发明具有以下优点:本发明通过引入动态共价键并结合退火工艺,能够有效改善复合材料界面处的应力状态。动态共价键在退火过程中发生可逆交换反应,促使树脂基体内部的交联网络重构,改善复合材料界面处的应力状态。实验结果表明,采用本发明方法制备的复合材料界面结合强度提升20%-60%。显著改善了复合材料的界面结合性能,本发明方法工艺简单,无需复杂的设备或额外的界面改性剂,易于实现大规模工业化生产。与传统方法相比,本发明减少了工艺步骤和成本,提高了生产效率。有效降低复合材料中不均匀分布的应力,提高复合材料的界面强度以及服役稳定性,进而提高复合材料的应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958736A_ABST
    Figure CN122958736A_ABST
Patent Text Reader

Abstract

A method for improving the interface strength of a fiber composite material, in which a prepolymer of an epoxy resin containing dynamic covalent bonds is prepared, the prepolymer of the epoxy resin is cast in a mold, a fiber bundle is inserted into the prepolymer of the epoxy resin to form a fiber bundle prepolymer; the fiber bundle prepolymer is cured to obtain a fiber bundle composite material, the cured fiber bundle composite material is air-cooled to room temperature at a rate of 20-30°C / min; the fiber bundle composite material is annealed at different annealing temperatures for a predetermined time, and then cooled to room temperature at a rate of 0.5-1°C / min, to obtain fiber bundle composite materials with different interface strengths.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fiber composite materials technology, and in particular to a method for improving the interfacial strength of fiber composite materials. Background Technology

[0002] Carbon fiber reinforced resin matrix composites are widely used in aerospace, automotive manufacturing, and other fields due to their excellent properties such as high specific strength, high specific modulus, and corrosion resistance. However, during the curing process, the resin shrinkage and the difference in thermal expansion coefficients between the resin matrix and carbon fibers can generate significant internal stress in the interfacial region, leading to a decrease in interfacial bonding strength and affecting the overall mechanical properties and service life of the material. Improving the overall mechanical properties and service life of composite materials has become a significant technical challenge in the industrial manufacturing of composite materials.

[0003] Traditional methods primarily alleviate internal stress by optimizing the curing process or adding interfacial modifiers. In terms of curing process optimization, techniques such as staged curing, gradient heating, or post-curing treatment are commonly used to attempt to reduce internal stress accumulation by controlling the temperature and stress fields during curing. However, these methods often require complex process parameter control and have limited effectiveness, failing to fundamentally solve the problem of stress concentration within the interface. Furthermore, curing process optimization is limited by factors such as the material system and molding equipment, making it difficult to widely apply to different types of composite materials. Regarding interfacial modification, common methods include coating the carbon fiber surface with coupling agents, nanoparticles, or polymer coatings to improve the interfacial compatibility between the resin matrix and the carbon fiber. For example, silane coupling agents can enhance interfacial bonding through chemical bonding, while nanoparticles can alleviate internal interfacial stress through physical filling and stress transfer mechanisms. However, these interfacial modification methods also have some limitations: firstly, the introduction of modifiers may increase process complexity, especially in large-scale production, making it difficult to ensure uniform distribution of the modifier in the interfacial region; secondly, some modifiers may affect other properties of the composite material, such as electrical conductivity, thermal conductivity, or heat resistance. In summary, the limitations of the aforementioned methods for mitigating interfacial internal stress are key factors restricting the regulation and performance optimization of composite material interfacial stress.

[0004] The information disclosed in the background section is only for enhancing the understanding of the background of this invention, and therefore may contain information that does not constitute prior art known to those skilled in the art. Summary of the Invention

[0005] This invention provides a method for improving the interfacial strength of fiber composite materials, effectively enhancing the interfacial strength of composite materials and solving the problem of interfacial failure caused by interfacial stress concentration in traditional methods.

[0006] A method for improving the interfacial strength of fiber composite materials includes: Epoxy resin prepolymers containing dynamic covalent bonds are combined with fibers to form fiber-reinforced prepregs; The fiber-reinforced prepreg is cured to form a cross-linked network in the resin matrix, thereby obtaining a fiber composite material. The cured fiber composite material is annealed. At the annealing temperature, the dynamic covalent bonds at the interface undergo a reversible exchange reaction, which optimizes the stress distribution at the fiber-resin interface and enhances the interfacial bonding strength. The cooling rate is controlled to form a stable fiber composite material.

[0007] The method for improving the interfacial strength of fiber composite materials can be used in all fiber composite materials containing dynamic chemical bonds, which include one or more of ester bonds, disulfide bonds, imine bonds, or borate ester bonds.

[0008] In the method for improving the interfacial strength of fiber composite materials, the curing process parameters include a curing temperature of 60℃-180℃ and a curing time of 1-24 hours.

[0009] In the method for improving the interfacial strength of fiber composite materials, the composite material is annealed after curing. During the annealing process, the dynamic covalent bonds undergo a reversible exchange reaction, and the crosslinked network inside the resin matrix is ​​reconstructed.

[0010] In the method for improving the interfacial strength of fiber composite materials, the composite material is subjected to an annealing process after curing, wherein the annealing temperature includes 120°C-220°C and the annealing time includes 1-2 hours.

[0011] In the method for improving the interfacial strength of fiber composite materials, the cooling rate after annealing includes 0.5-1°C / min furnace cooling to room temperature.

[0012] In the method for improving the interfacial strength of fiber composite materials, the diameter of the fiber bundle includes 7 μm.

[0013] A fiber composite material prepared by the method described above.

[0014] In the aforementioned fiber composite material, the fiber composite material is a fiber bundle, and the fibers include, but are not limited to, carbon fiber and glass fiber.

[0015] In the aforementioned fiber composite material, compared with the unannealed fiber bundle composite material, the interfacial bonding strength of the annealed fiber composite material is increased by 20%-60%.

[0016] Compared with existing technologies, this invention has the following advantages: By introducing dynamic covalent bonds and combining them with an annealing process, this invention can effectively improve the stress state at the interface of composite materials. The dynamic covalent bonds undergo a reversible exchange reaction during annealing, promoting the reconstruction of the cross-linked network within the resin matrix and improving the stress state at the composite material interface. Experimental results show that the interfacial bonding strength of composite materials prepared using this method is increased by 20%-60%. It significantly improves the interfacial bonding performance of composite materials. The method of this invention is simple, requires no complex equipment or additional interfacial modifiers, and is easy to implement for large-scale industrial production. Compared with traditional methods, this invention reduces process steps and costs, and improves production efficiency. It effectively reduces unevenly distributed stress in composite materials, improves the interfacial strength and service stability of composite materials, and thus enhances the application potential of composite materials. Attached Figure Description

[0017] Various other advantages and benefits of the present invention will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. It is obvious that the drawings described below are merely some embodiments of the invention, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort. Furthermore, the same reference numerals denote the same parts throughout the drawings.

[0018] In the attached diagram: Figure 1 This is a flowchart of the method for preparing composite materials containing dynamically covalently bonded fiber bundles according to the present invention; Figure 2 This is a SEM image of the fiber prepreg effect of the composite material containing dynamic covalent bonds of the present invention; Figure 3 This is a schematic diagram illustrating the principle of stress homogenization in the composite material containing dynamically covalent fiber bundles of the present invention. Figure 4 This is a comparison diagram of the interfacial strength of the composite material containing dynamically covalent fiber bundles of the present invention at different annealing temperatures; Figure 5 This is a comparison diagram of the interfacial strength of the composite material containing dynamic covalent bonds of the present invention under different annealing times.

[0019] The present invention will be further explained below with reference to the accompanying drawings and embodiments. Detailed Implementation

[0020] Specific embodiments of the invention will now be described in more detail with reference to the accompanying drawings. While specific embodiments of the invention are shown in the drawings, it should be understood that the invention may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0021] It should be noted that certain terms are used in the specification and claims to refer to specific components. Those skilled in the art will understand that different terms may be used to refer to the same component. This specification and claims do not distinguish components based on differences in terminology, but rather on differences in function. The terms "comprising" or "including" used throughout the specification and claims are open-ended and should be interpreted as "comprising but not limited to." The following descriptions are preferred embodiments for carrying out the invention; however, these descriptions are for the purpose of understanding the general principles of the specification and are not intended to limit the scope of the invention. The scope of protection of this invention is determined by the appended claims.

[0022] To facilitate understanding of the embodiments of the present invention, further explanations and descriptions will be provided below with reference to the accompanying drawings and specific embodiments. The accompanying drawings do not constitute a limitation on the embodiments of the present invention.

[0023] Methods to improve the interfacial strength of fiber composites include the following steps: Epoxy resin prepolymers containing dynamic covalent bonds are combined with fibers to form fiber-reinforced prepregs; The fiber-reinforced prepreg is cured to form a cross-linked network in the resin matrix, thereby obtaining a fiber composite material. The cured fiber composite material is annealed. At the annealing temperature, the dynamic covalent bonds at the interface undergo a reversible exchange reaction, which optimizes the stress distribution at the fiber-resin interface and enhances the interfacial bonding strength. The cooling rate is controlled to form a stable fiber composite material.

[0024] like Figures 1 to 5 As shown, the method for improving the interfacial strength of fiber composite materials includes the following steps: An epoxy resin prepolymer containing dynamic covalent bonds is prepared, the epoxy resin prepolymer is cast into a mold, and carbon fiber bundles are inserted into the epoxy resin prepolymer to form a fiber bundle prepolymer. The fiber bundle prepolymer is cured to obtain a fiber bundle composite material. The cured fiber bundle composite material is air-cooled to room temperature at 20-30°C / min. The high cooling rate can quickly reduce the material from a high temperature to below the glass transition temperature, so that the dynamic ester bonds are "frozen" in the state where the stress is not completely released, and the initial residual stress is retained. The fiber bundle composite material was annealed at different annealing temperatures for predetermined times, and then cooled to room temperature in the furnace at a rate of 0.5-1°C / min. The low cooling rate allows sufficient time for the dynamic ester bond reaction to undergo network rearrangement, thus obtaining fiber bundle composite materials under different stress states.

[0025] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, the dynamic covalent bond is selected from one or more of ester bonds, disulfide bonds, or imine bonds.

[0026] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, the fiber bundle composite material is obtained by curing at 140°C for 12 hours to ensure that the resin is fully cured.

[0027] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, the annealing temperature is 120°C-180°C and the annealing time is 1-2 hours to ensure that stress is fully released.

[0028] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, annealing is performed at 120°C, 140°C, 160°C, and 180°C for 1 hour, followed by furnace cooling to room temperature at a rate of 0.5-1°C / min, to obtain fiber bundle composite materials under different stress states. Annealing below 120°C results in a small change in internal stress, leading to poor improvement in interfacial strength, while annealing above 180°C causes thermal damage to the resin.

[0029] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, during the annealing process, dynamic covalent bonds undergo a reversible exchange reaction, and the crosslinked network inside the resin matrix is ​​reconstructed.

[0030] In a preferred embodiment of the method for improving the interfacial strength of fiber composite materials, the fiber bundle is a carbon fiber bundle with a diameter of 7 μm.

[0031] A fiber composite material prepared by the method described above.

[0032] In the aforementioned fiber composite material, the fiber composite material is a carbon fiber bundle.

[0033] In the aforementioned fiber composite material, the interfacial bonding strength with the unannealed fiber composite material is increased by 20%-60%.

[0034] In one embodiment, a dynamic covalent network structure was constructed in an epoxy resin matrix. By controlling the annealing temperature, a reversible bond exchange reaction was induced in the composite material, achieving the reconstruction and optimization of the crosslinked network. This method can increase the interfacial strength of epoxy resin / carbon fiber by more than 60%.

[0035] In one embodiment, a method for improving the interfacial strength of fiber composite materials includes the following steps: Casting of epoxy resin prepolymer involves pouring epoxy resin prepolymer containing dynamic covalent bonds into a polytetrafluoroethylene (PTFE) mold. Applying a small amount of silicone grease to the surface of the PTFE mold ensures easy demolding and a smooth surface after molding of the composite material. T700 carbon fiber bundles are inserted into the epoxy resin prepolymer at a 90-degree angle to ensure that the carbon fiber bundles are evenly distributed and fully impregnated with the resin matrix, forming a mixture of fiber bundle prepolymer and carbon fiber. The mixture was cured at 140°C for 12 hours to allow the epoxy resin prepolymer to fully crosslink and cure, forming a stable fiber bundle composite material. During the curing process, a good interfacial bond was formed between the resin matrix and the carbon fibers. After curing, the fiber bundle composite material was removed from the mold and air-cooled to room temperature. At this point, significant stress was observed within the composite material, mainly concentrated in the interfacial region between the resin matrix and the carbon fibers. The cured fiber bundle composite material was annealed at different temperatures (120°C, 140°C, 160°C, and 180°C) for 1 hour, and then cooled to room temperature in the furnace. During the annealing process, the dynamic covalent bonds underwent a reversible exchange reaction at high temperature, which promoted the reconstruction of the crosslinked network inside the resin matrix, resulting in a composite material with optimized interfacial properties.

[0036] Preferably, the dynamic covalent bond of the epoxy resin is an ester bond.

[0037] Preferably, the diameter of a single carbon fiber in the T700 fiber bundle is 7 μm.

[0038] Preferably, the fiber bundle composite material is cured at 140°C for 12 hours.

[0039] Preferably, the cooling rate of the fiber composite material in air is 20°C / min.

[0040] Preferably, the annealing temperature of the fiber composite material is 120°C, 140°C, 160°C, or 180°C, and the annealing time is 1 hour.

[0041] Preferably, the cooling rate of the fiber bundle composite material after annealing in the furnace is 0.5-1°C / min.

[0042] In one embodiment, carbon fiber reinforced resin matrix composites are widely used in aerospace, automotive manufacturing, and other fields due to their excellent properties such as high specific strength, high specific modulus, and corrosion resistance. However, during the curing process, the resin curing shrinkage and the difference in thermal expansion coefficients between the resin matrix and carbon fibers can cause significant stress concentration in the interfacial region, leading to a decrease in interfacial bonding strength. The method of this invention can effectively improve interfacial strength and solve the problem of interfacial failure caused by interfacial stress concentration.

[0043] In this invention, the preparation method of the composite material containing dynamically covalent fiber bundles is as follows: Figure 1 As shown, the specific steps include: (1) Prepolymer preparation: epoxy monomers, curing agents and catalysts in dynamic covalent epoxy resin are mixed in proportion to form a uniform epoxy resin prepolymer. Among them, the dynamic covalent bond is preferably an ester bond because it has excellent reversible exchange properties. (2) Casting and fiber laying: the prepared prepolymer is cast into a polytetrafluoroethylene mold and T700 carbon fiber bundles (single filament diameter 7 μm) are inserted along the 90° direction to ensure that the fibers are evenly distributed and fully impregnated with the resin. (3) Curing and molding: the fiber bundle resin matrix composite material is completely cross-linked and cured after high temperature curing to form a fiber bundle composite material. After curing, it is cooled to room temperature in air. At this time, the material has significant internal stress. The stress is observed by SEM. Figure 2 It was found that in the composite material prepared by the method of the present invention, the epoxy resin had a better wetting effect on the carbon fiber and the interface bonding was tight. (4) Annealing treatment: The cured composite material was annealed and then cooled in the furnace. During the annealing process, the dynamic covalent bonds underwent reversible exchange reactions (such as Figure 3 As shown in the figure, network reconstruction is achieved.

[0044] The method of the present invention is applicable to improving the interfacial mechanical properties of composite materials containing dynamic covalent bonds. The epoxy resin containing dynamic covalent bonds can also be combined with other reinforcing phase materials other than carbon fibers to reduce the interfacial stress concentration of other reinforced composite materials and improve the interfacial strength. The reinforcing phase materials include fiber materials, which can be selected from glass fibers or polymer fibers, and particulate materials, which can be selected from carbon nanotubes, silica, ceramic particles, etc.

[0045] Introduction of Dynamic Covalent Bonds: The fiber bundle composite material releases internal stress through the introduction of dynamic bond exchange reactions. Dynamic ester bonds are introduced into the epoxy resin prepolymer. Specific materials and formulations are as follows: the epoxy monomer is bisphenol A type epoxy resin (DGEBA), the curing agent is glutaric anhydride (GA), and the catalyst is zinc acetone (Zn(acac)2), with a molar ratio of epoxy groups: anhydride groups: catalyst = 2:1:0.1. During the curing process, the epoxy resin prepolymer containing dynamic covalent bonds is mixed with T700 carbon fiber bundles and cured at 140℃ for 12 hours to ensure full bonding between the resin matrix and the carbon fibers. Annealing treatment involves annealing the cured composite material at different temperatures (120℃, 140℃, 160℃, 180℃) for 1 hour to release interfacial internal stress and improve interfacial bonding strength through dynamic bond exchange reactions.

[0046] Interfacial strength characterization: The fiber bundle specimen was clamped in the tensile fixture of a universal testing machine, ensuring that both ends of the specimen were firmly fixed. Tensile tests were conducted at a tensile rate of 2 mm / min, and the load-displacement curve was recorded. The maximum peak force was obtained from the load-displacement curve and divided by the cross-sectional area of ​​the specimen to calculate the interfacial strength. The interfacial strength under different heat treatment conditions (120℃, 140℃, 160℃, 180℃) was compared to analyze the effect of annealing temperature on interfacial bonding strength. Experimental results show that the interfacial bonding strength significantly increases with increasing annealing temperature, up to 60% or more. By adjusting the type and content of dynamic covalent bonds and annealing process parameters, the interfacial properties of the composite material were optimized. The strength comparison results are as follows: Figure 4 , Figure 5 As shown, the fiber bundle composite material annealed at 180 °C has the highest interfacial strength because it releases internal stress most completely.

[0047] The dynamic covalent polymer matrix composites of the comparative examples and Examples 1-6 of this invention were all prepared according to the following steps: Comparative Example Comparative Example 1: First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific procedure was as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The prepared prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured sample was directly removed and air-cooled at a rate of 20°C / min. The fiber bundle composite was prepared into standard specimens, and transverse tensile tests were conducted to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength reached 18.2 MPa. All test data are the average of three parallel samples. The key parameter control accuracy was as follows: temperature ±1°C, time ±1 min, and interfacial strength as shown. Figure 4 As shown. Example Example 1

[0048] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific steps were as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetonate was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured samples were annealed at 120°C for 1 hour and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 120°C reached 22.2 MPa, representing a 22% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 4 As shown. Example 2

[0049] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific steps were as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12 hours was used. The cured samples were annealed at 140°C for 1 hour and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 140°C reached 26.3 MPa, representing a 45% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 4 As shown. Example 3

[0050] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific steps were as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured samples were annealed at 180°C for 1 hour and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 180°C reached 29.4 MPa, representing a 62% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 4 As shown. Example 4

[0051] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific procedure was as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured samples were annealed at 160°C for 0.5 hours and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 160°C reached 23.5 MPa, representing a 29% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 5 As shown. Example 5

[0052] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific steps were as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured samples were annealed at 160°C for 1 hour and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 160°C reached 28.6 MPa, representing a 57% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 5 As shown. Example 6

[0053] First, an epoxy resin prepolymer containing dynamic ester bonds was prepared. The specific steps were as follows: Bisphenol A type epoxy resin was preheated to 130°C, then zinc acetylacetone was added and stirred for 30 minutes. Subsequently, glutaric anhydride curing agent was added and stirred at 80°C for 30 minutes, followed by vacuum degassing for 60 minutes. The obtained prepolymer was then impregnated with T700 carbon fibers (7 μm monofilament diameter) at 80°C to ensure full wetting. A curing process of 140°C / 12h was used. The cured samples were annealed at 160°C for 2 hours and then furnace cooled at a rate of 0.5°C / min. The heat-annealed fiber bundle composites were prepared into standard specimens, and transverse tensile tests were performed to evaluate the interfacial bond strength. Performance test results showed that the interfacial strength of the sample annealed at 160°C reached 29.1 MPa, representing a 60% increase compared to the comparative example. All test data are the average of three parallel samples. The key parameters were controlled with the following precision: temperature ±1°C, time ±1 min, and interface strength as follows. Figure 5 As shown.

[0054] Although embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the specific embodiments and application fields described above. The specific embodiments described above are merely illustrative and instructive, and not restrictive. Those skilled in the art can make many other forms based on the guidance of this specification and without departing from the scope of protection of the claims of the present invention, and all of these are within the scope of protection of the present invention.

Claims

1. A method for improving the interfacial strength of fiber composite materials, characterized in that, The method includes: Epoxy resin prepolymers containing dynamic covalent bonds are combined with fibers to form fiber-reinforced prepregs; The fiber-reinforced prepreg is cured to form a cross-linked network in the resin matrix, thereby obtaining a fiber composite material. The cured fiber composite material is annealed. At the annealing temperature, the dynamic covalent bonds at the interface undergo a reversible exchange reaction, which optimizes the stress distribution at the fiber-resin interface and enhances the interfacial bonding strength. The cooling rate is controlled to form a stable fiber composite material.

2. The method for improving the interfacial strength of fiber composite materials according to claim 1, characterized in that, Preferably, it can be used in all fiber composites containing dynamic chemical bonds, including one or more of ester bonds, disulfide bonds, imine bonds, or borate ester bonds.

3. The method for improving the interfacial strength of fiber composite materials according to claim 1, characterized in that, The curing process parameters include a curing temperature of 60℃-180℃ and a curing time of 1-24 hours.

4. The method for improving the interfacial strength of fiber composite materials according to claim 1, characterized in that, After curing, the composite material undergoes an annealing process. During annealing, dynamic covalent bonds undergo reversible exchange reactions, and the cross-linked network inside the resin matrix is ​​reconstructed.

5. The method for improving the interfacial strength of fiber composite materials according to claim 1, characterized in that, After curing, the composite material undergoes an annealing process, with the annealing temperature ranging from 120°C to 220°C and the annealing time ranging from 1 to 2 hours.

6. The method for improving the interfacial strength of fiber composite materials according to claim 1, characterized in that, The cooling rate after annealing includes 0.5-1°C / min furnace cooling to room temperature.

7. The method for improving the interfacial strength of fiber composite materials according to claim 1, preferably, the diameter of the fiber bundle includes 7 μm.

8. A fiber composite material, characterized in that, It is prepared by the method described in any one of claims 1-7.

9. The fiber composite material according to claim 8, characterized in that, Fiber composites are fiber bundles, and the fibers include, but are not limited to, carbon fiber and glass fiber.

10. The fiber composite material according to claim 8, characterized in that, Compared with unannealed fiber bundle composites, the interfacial bonding strength of annealed fiber composites is improved by 20%-60%.